Genesis of the Concept and Process of Strategizing at Enterprises - Iastremska, Olesia A. (Problemi ekonomìki, 2023)
The aim of the article is to summarize theoretical proposals on the definition of the concept of strategizing, to study its genesis and the need to use it in the complex modern conditions of life of enterprises, to clarify the components and stages of the strategizing process and their features, to determine the purpose of strategizing in the conditions of the experience economy as the most progressive model of economic relations, which ensures the growth of added value and profit of enterprises. The object of the research is a complex socioeconomic phenomenon of strategizing and the process of its implementation; the subject is theoretical provisions, conceptions, methodology of enterprise strategizing and their application in the conditions of the experience economy. The following main methods were used in the research process: system approach, method of structural-logical analysis, theoretical generalization, scientific abstraction, concretization and comparative analysis, historical and logical analysis, process approach, theoretical generalization. The article presents the modern features of the internal environment and the external environment of enterprises, which determine the development of the concept of strategizing and the process of its implementation. The main stages of development of strategic management of enterprises with identification of strategizing have been proposed. In chronological order, the definition of the concept of strategizing and its stages and components from its origin to the present (2023) in the scientific works of foreign and domestic scholars is examined and systematized, taking into account the latest trends in changes in economic relations and the feasibility of using in the model of the experience economy. On the basis of generalization of the proposals of scholars and the existing economic realities, an understanding of the concept of strategizing enterprises as the main way of strategic thinking about the future of enterprise is proposed, the main components and stages of the process of its course include the definition of the mission, vision, goals of the enterprise’s life, analysis of factors of the internal and external environment in accordance with the set goals, determination of the strategic instruments (system of strategies) of the enterprise’s life, substantiation of criteria for the selection of strategies, which in the conditions of the experience economy are aimed at highlighting the attractiveness of the enterprise, the strength and value of its brand and the level of reputation, making decisions on the final composition of the set of strategies, forecasting the trajectories of the enterprise in accordance with the adopted strategies and taking into account possible scenarios of the course of events, the implementation of organizational and communication foresightings, the implementation of adopted strategies in accordance with the approved strategic plan of the enterprise.